Adolescent Mental Health and Suicidality in Nepal: A Systematic Review of Prevalence, Risk Factors, and Protective Factors - Giri, Suja; Bhandari, Mamata; Pathak, Pitambar; Bhatta, Pramish; Shrestha, Romi; Khatiwada, Sushma; Adhikari, Sanjita; Khanal, Ashish (Journal of Multidisciplinary Research Advancements, 2026)
Adolescent mental health is a critical global public health concern, with suicide being a leading cause of death among youth. In Nepal, a low-income country undergoing rapid socio-economic change, adolescents face unique stressors that may exacerbate this risk, but a synthesized overview of the evidence is lacking. This systematic review aimed to synthesize the current evidence on the prevalence, risk factors, and protective factors associated with mental health conditions and suicidality among adolescents in Nepal. We conducted a systematic search of four electronic databases (PubMed/MEDLINE, PsycINFO, Web of Science, Scopus), following PRISMA guidelines. Observational and qualitative studies investigating mental health or suicidality in Nepalese adolescents (aged 10-19) were included. Study selection, data extraction, and thematic analysis were performed by two independent reviewers using ATLAS.ti software. The review included 75 studies. Findings reveal alarmingly high prevalence rates: depressive symptoms (41.6-42.8%), anxiety (56.9%), suicidal ideation (13.6-30.9%), and non-suicidal self-injury (44.8%). A complex web of risk factors was identified, dominated by severe academic stress, exposure to violence (particularly sexual harassment), familial discord and lack of support, and comorbid psychological distress. Pervasive stigma was the primary barrier to care, contributing to a massive treatment gap. Protective factors were primarily relational, including strong peer connections and family cohesion. Adolescents in Nepal are experiencing a mental health crisis characterized by high distress and suicidality, driven by a toxic synergy of socio-ecological risks and systemic failures in support and care. Urgent, multi-level interventions are required, including integrated school-based mental health programs, community stigma reduction, strengthened child protection, and the development of accessible, adolescent-friendly services.